Partnership of parent and teacher in the context of inclusive practice - Dedaj, Marta D. (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2021)
Inclusion refers to the active participation of children with disabilities in their immediate and wider environment in accordance with their abilities. The paper focuses on the partnership of educators and parents in the context of real inclusive practice, through a strategy of support for children with disabilities. The theoretical basis is a systems approach, which implies the understanding that the studied system is part of a broader system and that the system itself consists of smaller subsystems that are mutually conditioned. A systematic approach to inclusion provides a conceptual framework for determining the combined impact on preschool children in a dynamic relationship with their environment. It can be concluded that inclusion requires partnership work and that one of the priority tasks of an inclusive preschool institution is to develop quality support programs and involve parents in children’s activities.